Texture synthesis of ecological plant protection image based on convolution neural network - Hu, Libing; Zhou, Fei; Fu, Xianjun (Frontiers in Plant Science, 2022)
Texture synthesis technology is an important realistic rendering technology. Texture synthesis technology also has a good application prospect in image rendering and other fields. Convolutional neural network is a very popular technology in recent years. Convolutional neural network model can learn the features in data and realize intelligent processing through the feature learning in data. Later, with the rapid improvement of convolutional neural network, texture synthesis technology based on neural network came into being. The purpose of this paper is to study the texture synthesis method of ecological plant protection image based on convolutional neural network. In the experiment, the experimental environment is established, and the subjective evaluation and objective evaluation of the image texture synthesis method experiment are investigated and studied by using swap algorithm. The experimental results show that the method used in this paper is superior to other methods.